GAYA BICARA PADA STAF PENGAJAR JURUSAN AKUNTANSI POLITEKNIK NEGERI SEMARANG DI DALAM KEGIATAN PROSES BELAJAR MENGAJAR - Pandiya Pandiya Pandiya; Nurul Hamida Hamida (Politeknik Negeri Semarang, 2019)
This study aims to determine the extent to which the teaching staff in the Semarang State Polytechnic Accounting Department applies a style of speech; i.e. either oratory, deliberative, consultative, relaxed, or intimate. The data collection is done by questionnaire and class observation. The population of this study consists of teaching staff at the Semarang State Polytechnic Accounting Department. The data is more qualitative, which is more in the form of a description of the characteristics of the respondents and not much related to the numbers. Sampling technique is done by population, namely all teaching staff of Semarang State Polytechnic Accounting Department. Data analysis is carried out by a Likert Scale of 5. The results indicate that Consultative Speech is the style most widely applied by the Teaching Staff of the Semarang State Polytechnic Accounting Department, while the oratoric speaking style is the least practiced style. Extemporan presentation method is the most widely applied method in the activities of the Teaching and Learning Process in the Semarang State Polytechnic Accounting Department, while the impromptu method is the least applied method. The most widely used body language is a smile, while eye flicker is the least applied body language. The distance between the Teaching Staff and Students in the Teaching and Learning Process activities that are most widely applied are groups (125-350 cm), while the least applied distance is intimate (50 cm). The results of this study support the previous research that the use of Body Language greatly affects the success of the Teaching and Learning process.